Rate Hikes and Bank Spikes: An Empirical Study of Monetary Policy Pass-Through in Sweden - Thuresson,Carl (2024)
This paper examines monetary policy pass-through onto banks’ interest rates in Sweden, exploring variations across different bank categories and periods of policy rate adjustments. Using a Vector Error Correction Model (VECM) with daily data from 1985 to 2024 and a newly developed interest rate sensitivity analysis, this study analyzes short- and long-term pass-through effects on both lending and saving rates, with a special focus on the negative policy rate regime in 2015-2020. Results reveal significant variations in pass-through across bank categories and policy rate changes, with a structural break in 2015 reducing monetary policy pass-through, especially for mortgage rates, leading to pass-through on saving rates exceeding that of lending rates, contradicting previous research. Lending rates adjust faster compared to saving rates during policy rate increases while saving rates adjust faster than lending rates during policy rate decreases, indicating banks’ use of market power to boost profits during rate changes, which is especially true for larger banks. Pass-through was heavily hampered during the negative policy rate regime, with some signs of reversal in pass-through direction. Understanding these nuanced dynamics is crucial for monetary policy authorities to accurately assess the transmission mechanism of policy rate changes and their implications for the broader economy.
Keywords: Monetary Policy Pass-Through; Bank Interest Rates; Vector Error Correction Model; Interest Rate Beta; Sweden